Possibility of early withdrawal of benzodiazepine hypnotics by combination with ramelteon for the treatment of insomnia: A pilot study. Issue 1 (18th January 2013) - Furuya, Motohide; Miyaoka, Tsuyoshi; Wake, Rei; Nagahama, Michiharu; Kawano, Kiminori; Yamashita, Satoko; Ieda, Masa; Ezoe, Satoko; Horiguchi, Jun
Abstract We performed a prospective observational study in 70 subjects (50 subjects with insomnia associated with mental disorders and 20 subjects with primary insomnia) receiving ramelteon (RMT) 8 mg/day for 8 weeks. Scores of clinical symptoms by self‐assessment in every category significantly improved in all subjects after 2 weeks of RMT administration; subsequently, the scores improved with continuous administration. At week 8, most of the subjects had a score of 3 (good). The dose of benzodiazepine (BZ) hypnotics coadministered in 50 subjects was reduced with an improvement in the score, and 23 subjects had achieved "RMT single‐use" by week 8. Our study shows that the administration of RMT in combination with BZ hypnotics improves the clinical symptoms of subjects with or without mental disorders early after the start of RMT administration, and the dose of BZ hypnotics can be tapered or administration can be discontinued while maintaining symptom improvement. The results suggest that continuous administration of RMT at least for 1 month would be ideal in order to reduce BZ hypnotics coadministered. RMT might be safe and easy to use for healthcare professionals in various fields because of its unique profile that is different from that of traditional hypnotics.